Some thoughts on resetting the roles and functions ofSharīʿah committees of Islamic banks in Malaysia - Md. Isa Mansor; Siew Peng Lee; Obiyathulla Ismath Bacha; Rubi Ahmad (ISRA International Journal of Islamic Finance, 2022)
Purpose - The purpose of this study is to understand and evaluate the roles and functions of the Sharīʿah committee (SC) of Islamic banks (IBs) in Malaysia and to recommend a resetting of the scope of responsibilities to enable the SC to effectively respond to current market needs. Design/methodology/approach - A Likert-type survey questionnaire was developed and distributed to all available SC members through e-mails and online surveys as well as self-administered questionnaires. At the end of the survey, 87 useable questionnaires were collected from 161 SC members, representing a 54% response rate. Findings - This study finds that most SC members have the necessary Sharīʿah qualification, and they are mostly academics with doctoral degrees. However, there is a noticeable lack of diversity in the composition of experts in the committees. Respondents indicate that their main functions are to ensure Sharīʿah compliance of bank operations and product offerings. This is of course consistent with their stated functions as outlined in the Bank Negara Malaysia's Sharīʿah Governance Policy Document (BNM, 2019). The study finds that SCs are not involved in product development, nor responsible for financial performance. Respondents indicate three ways to enhance the role of SCs: improving banking knowledge of the members, more engagement with the board of directors (BoDs) and broadening the functions of SCs. Practical implications - This study highlights two policy implications. First, there is a strategic need for IBs to consider having a diversity of expertise in the SCs while maintaining the Sharīʿah experts as core members. Second, this study recommends a reset of the scope of duties of the SC to include three new areas: risk management, product development and financial performance. Originality/value - This study evaluates the current functions of the SC of IBs in Malaysia and provides suggestions for improvement in the composition of the committee and in the scope of duties of SCs based on contemporary needs.
Keywords: 330; Islamic banks; Malaysia; Sharīʿah committee; Sharīʿah compliance